2022
DOI: 10.1038/s41541-022-00571-0
|View full text |Cite
|
Sign up to set email alerts
|

A potent, broadly protective vaccine against SARS-CoV-2 variants of concern

Abstract: Since the first outbreak in December 2019, SARS-CoV-2 has been constantly evolving and five variants have been classified as Variant of Concern (VOC) by the World Health Organization (WHO). These VOCs were found to enhance transmission and/or decrease neutralization capabilities of monoclonal antibodies and vaccine-induced antibodies. Here, we successfully designed and produced a recombinant COVID-19 vaccine in CHO cells at a high yield. The vaccine antigen contains four hot spot substitutions, K417N, E484K, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…This could be related to the notion that K417N/T and E484K substitutions shared by Beta and Gamma viruses simulate a structure that enhances the spectrum of neutralizing activity. In agreement with this hypothesis and our results, a study evaluating the immunogenicity of an S-protein sequence containing these three substitutions in addition to D614G (B.1) demonstrated that the variant vaccine is capable of eliciting high neutralizing Ab titers that cross-reacted with five VOCs in NHP 27 . Moreover, in preclinical and clinical trials Beta derived vaccines induced broadly neutralizing antibodies that can cross-react against different VOC 27,28 in a similar way than the Gamma derived vaccine presented in this work.…”
Section: Discussionsupporting
confidence: 90%
“…This could be related to the notion that K417N/T and E484K substitutions shared by Beta and Gamma viruses simulate a structure that enhances the spectrum of neutralizing activity. In agreement with this hypothesis and our results, a study evaluating the immunogenicity of an S-protein sequence containing these three substitutions in addition to D614G (B.1) demonstrated that the variant vaccine is capable of eliciting high neutralizing Ab titers that cross-reacted with five VOCs in NHP 27 . Moreover, in preclinical and clinical trials Beta derived vaccines induced broadly neutralizing antibodies that can cross-react against different VOC 27,28 in a similar way than the Gamma derived vaccine presented in this work.…”
Section: Discussionsupporting
confidence: 90%
“…Zhongshan Kangtian Shenghe Biotechnology Co., Ltd., QuaCell, one of our partners, obtained the original adherent CHO-K1 cell from Public Health England (PHE) in England. The cells were domesticated in serum-free and suspension culture (protected by patent application) by them, and the cell lines have also been used in previous publications [ 18 , 19 ]. Glu-C and trypsin, both sequencing grade, were purchased from Roche and Sigma-Aldrich, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, there is a need to develop broadly protective next-generation SARS-CoV-2 vaccines that will provide better protection against emerging VOCs and further reduce virus shedding and transmission among the vaccinated population. These pan-SARS-CoV-2 VOC vaccine candidates will also inform the development of broadly protective pan-Sarbecovirus and pan-Betacoronavirus vaccine candidates 26 , some of which have been published recently 25,27,28 .…”
Section: Introductionmentioning
confidence: 99%